Civic Education as the Embodying of National Identity for Students in Elementary Schools - Ni Putu Suparmini; Dewa Bagus Sanjaya; I Nengah Suastika (Universitas Pendidikan Ganesha, 2025)
Civic Education (PKn) holds a crucial role in shaping and manifesting students’ national identity from an early age. However, a notable discrepancy exists between the normative expectations (das sollen) and the practical realities (das sein) of its implementation in elementary schools. While the PKn curriculum is ideally designed to instill national values such as Pancasila, the spirit of unity in diversity (Bhinneka Tunggal Ika), and patriotism, its application in classrooms often remains conventional, less engaging, and disconnected from students’ real-life contexts. As a result, students struggle to internalize the intended values meaningfully. This study aims to analyze Civic Education as a medium for fostering national identity among elementary school students through a comprehensive literature review. Utilizing a qualitative library research approach, this study draws on scholarly journals, academic books, and official documents relevant to the topic. The findings reveal that PKn can effectively strengthen national identity when implemented through interactive and contextual learning strategies, such as integrating national values into the curriculum, adopting innovative teaching methods, and promoting extracurricular activities that reinforce national character. With appropriate pedagogical approaches, Civic Education can serve as a transformative tool to cultivate students’ critical awareness, deepen their understanding of national values, and empower them to uphold unity and national integrity amid the challenges of globalization.